Accidental Insertion of a Broken Needle into the Pterygoid Mandibular Space during Inferior Alveolar Nerve Block: A Case Report - Kazuhiro Terada; Kenji Yamagata; Fumihiko Uchida; Satoshi Fukuzawa; Naomi Ishibashi-Kanno; Hiroki Bukawa (Case Reports in Dentistry)
The incidence of needle breakage is estimated to be 0.000007%, and most needle breaks occur during inferior alveolar nerve block (IANB) administration and are localized to the pterygomandibular space. Although immediate surgical intervention is recommended for the removal of the fracture needles, intraoperative localization of a broken injection needle fragment can be challenging. Here, we present the case of a 36-year-old woman who underwent dental extraction of the left lower wisdom tooth under local anesthesia at a private office. At that time, a disposable 33G needle was broken and accidentally inserted into the pterygomandibular space during IANB. A broken injection needle was presented at the base of the left coronoid process of the mandible on computed tomography (CT). We successfully removed the broken injection needle using fluoroscopy and assisted endoscopy under general anesthesia.